Cardiorespiratory and Neuromuscular Demand of Daily Centrifugation: Results From the 60-Day AGBRESA Bed Rest Study - Kramer, Andreas; Venegas-Carro, María; Mulder, Edwin; Lee, Jessica K.; Moreno-Villanueva, María; Bürkle, Alexander; Gruber, Markus (Frontiers in Physiology, 2020)
Purpose: Long stays in space require countermeasures for the degrading effects of weightlessness on the human body, and artificial gravity (AG) has been proposed as an integrated countermeasure. The aim of this study was to assess the cardiorespiratory and neuromuscular demand of AG elicited via daily centrifugation during 60 days of bed rest. Methods: 24 participants (33±9y, 175±9 cm, 74±10 kg, 8 female) were subjected to 60 days of strict six-degree head-down tilt (HDT) bed rest and were randomly allocated to one of three experimental groups: 30 minutes of daily centrifugation with an acceleration of 1g at the center of mass and 2g at the feet applied continuously (cAG) or intermittently in 6 epochs of 5 minutes each, separated by 3-minute breaks (iAG), or non-centrifuged control (CTRL). Cardiorespiratory demand during centrifugation was assessed at the beginning (HDT3) and end (HDT60) of the bed rest phase via spirometry and heart rate monitoring, leg muscle activation was monitored via electromyography. Results: On average, analyses of variance revealed that heart rate during centrifugation increased by 40% (iAG) and 60% (cAG) compared to resting values (p<0.001), while oxygen uptake did not change significantly (p=0.96). There was a preference for calf over knee extensor muscle activation (active time soleus 57±27%, gastrocnemius medialis 45±27% and vastus lateralis 27±27%, p<0.001), with large inter-individual differences in leg muscle active time. AG could not prevent the increase in resting heart rate after bed rest. For most of the recorded parameters, there were little differences between cAG and iAG, with the increase in heart rate during centrifugation being a notable exception (greater increase for cAG, p=0.01). Conclusion: Daily 30-minute bouts of artificial gravity elicited by centrifugation put a substantial demand on the heart as a pump without increasing oxygen consumption. If centrifugation is to be used as a countermeasure for the deteriorating effects of microgravity on physical performance, we recommend combining it with strenuous exercise.